Knowledge Sharing dalam Ekosistem UMKM: Perspektif Pelaku Usaha di Kota Padang - Chichi Andriani; Yunia Wardi; Susi Evanita; Hendrik Heri Sandi (Jurnal Ecogen, 2025)
This study aims to examine the perceptions of Micro, Small, and Medium Enterprises (MSMEs) towards knowledge sharing practices in Padang City. The research approach used is causal-quantitative, with primary data collection through distributing questionnaires to 90 MSME respondents. To support the empirical analysis, this study is also supplemented with secondary data through a systematic literature study of 12 relevant scientific articles, published between 2004 and 2024, and obtained from the Google Scholar and ScienceDirect databases. The results of the analysis show that the average Total Composite Rating (TCR) score for knowledge sharing practices is at 75.19%, which is included in the "quite good" category. Specifically, the knowledge donating dimension scored 74.93%, while knowledge collecting recorded a slightly higher score, namely 75.44%. This finding reflects that MSMEs have a positive level of awareness of the importance of knowledge sharing, but its implementation is still informal and has not been systematically documented. The results of the literature study support these findings, by showing that knowledge sharing practices in the global MSME sector tend to be unstructured and still lack technological support. Therefore, this study recommends the importance of developing a systematic knowledge sharing strategy and external support to build a collaborative culture in the MSME ecosystem